FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR - Juika, Fonny; Dewi, Sofia Prima (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to obtain empirical evidence of the effect of profitability, liquidity, firm size, asset structure, and sales growth on capital structure of manufacturing companies listed on the Indonesian Stock Exchange during the 2017-2020 period. In conducting this research, researchers used descriptive methods. The number of samples that have been selected based on criteria as many 76 data, in this study the sample was chosen because the researcher used a purposive sampling technique. Data processing using Eviews 12. The result shown in this study are that profitability have a positive effect on capital structure, while liquidity, asset structure, and sales growth have no positive effect on capital structure, firm size have no negative effect on capital structure. The implication of this study is that companies need to pay attention to profitability to maximize the company's capital structure.